Perancangan Turbin Francis untuk Pembangkit Listrik Tenaga Minihidro di Lhok Sandeng Kabupaten Pidie Jaya - - Azwinur; - Hamdani; Ahmad Syuhada (Jurnal Teknik Mesin Unsyiah, 2013)
The increase of population, followed by the increasing growth of the industry led to high demand of electricity. Many different ways have been done to find and use natural potential as electrical energy that can be used. The potential energy of water is one of the energy that can be converted into electrical energy maximally. One of still unused water potential energies is the water of Krueng Meureudu in Pidie Jaya. The river location is in Lhok Sandeng village, Meurah Dua sub district, Pidie Jaya. The width of the river ranges from 30 to 50 meter with the debit of about 10÷15 m3/ s. This can be used to generate electricity using Francis type water turbines to meet the energy requirements of the surrounding population. The first step in designing the turbine is to determine the turbine type based on the value of specific rotation (Ns) obtained from the head (H) and debit data (Q). Then, the design of main components, which are runner, shaft, spiral casing, guide vane and draft tube. Thus, based on the calculation, the dimensions and designs of the main components of the Francis turbine are obtained.